Development of Learning Tools Social Emotional Defense to Improve Learning Outcomes and Critical Thinking Skills in Human Reproductive System Materials in SMP Negeri 2 Intu Lingau - Raja Pagarlan Manurung; Didimus Tanah Boleng; Sonja V. T. Lumowa; Akhmad; Sukartiningsih; Taufan Purwokusumaning Daru; Elsje Theodora Maasawet; Vandalita Rambitan (Jurnal Penelitian Pendidikan IPA, 2024)
This study uses the type of development research by adapting the model designed by Borg and Gall (1983) by making modifications. This research developed a product in the form of a learning plan of the Human Reproductive System material with the application of social Emotional Competency (KSE) differentiation learning which was developed specifically with the hope of increasing learning outcomes and critical thinking skills of class IX students in the subject of the reproductive system at SMP Negeri 2 Intu Lingau, West Kutai Regency. The development procedure in this study includes seven stages, namely the preliminary stage, planning, developing the initial product form, initial field testing, main product revision, final product testing, and dissemination. The research instruments used in this study were: Questionnaire sheets validating the assessment of science learning tools, Questionnaire sheets for social emotional attitudes, observation sheets for the implementation of learning, and giving test questions. This development research used Aiken’s V data analysis technique to determine the validation value of learning tools and determine the student Gain to analyze students thinking skills. From the results of this study it was found that science learning tools with social emotional competence (KSE) which include syllabus, lesson plant, worksheets, assessment instruments, and teaching materials about the human reproductive system are appropriate based on the value of Aiken’s V validation coefficient. Development of learning Outcomes significantly in the experimental class based on the gain scores obtained.